A Theoretical Model Proposal: Personal Innovativeness and User Involvement as Antecedents of Unified Theory of Acceptance and Use of Technology - Turan, Aygul; Tunc, Aysegul Ozbebek; Zehir, Cemal (ELSEVIER SCIENCE BV, 2015)
An emerging stream of work on technology acceptance and innovation diffusion complements a large body of literature that points to users' technology acceptance behavior. In this paper, we argue theoretically that technology acceptance should be integrated into diffusion of innovation theory, so both concepts should be explained at the same framework. On the other hand, acceptance behavior is explained many other constructs, such as user satisfaction, user involvement. Unlike the previous research, we propose an overall framework to explain acceptance behavior and system implementation success. Hence we use unified theory of acceptance and use of technology. After that we try to create a linkage with this theory and personal innovativeness and user involvement as antecedents by providing some propositions. We will test these propositions in a field research for future research.
Keywords: Technology Acceptance Model; Innovation Diffusion Theory; Personal Innovativeness; User Satisfaction; User Involvement; Unified Theory of Acceptance and Use of Technology; INFORMATION-SYSTEMS SUCCESS; SATISFACTION; Business & Economics; Social Sciences - Other Topics